The effects of precarious employment and calling on the psychosocial health and work well-being of young and older workers in the care sector: a longitudinal study - Hult Marja; Kallio Hanna; Kangasniemi Mari; Pesonen Tanja; Kopra Juho (Springer, 2025)
Objective
Employment conditions in the care sector are changing, and precarious employment (PE) is becoming more widespread, manifesting as undervaluation, adverse leadership, work overload, and inadequate control over work. This study aimed to examine changes in psychosocial health, work well-being, PE, and calling over time and explore the effects of PE and calling on psychosocial health and work well-being.
Methods
The longitudinal study collected follow-up panel data in the three time points (2020, 2022, and 2023) from care workers (n = 1502), linear mixed effects models.
Methods
The longitudinal study collected follow-up panel data in the three time points (2020, 2022, and 2023) from care workers (n = 1502), linear mixed effects models.
Results
PE decreased (β =  – 0.02), and perceived work well-being increased (β = 0.04), but there were no change in psychosocial health (β =  – 0.01) and calling (β = 0.01) during the three-year period. Younger (< 39) care workers perceived higher levels of PE and had poorer psychological health. Moreover, PE had a negative effect on psychosocial health (β =  – 0.63) and work well-being (β =  – 0.68) and calling had a positive effect on psychosocial health (β = 0.41) and work well-being (β = 0.49) in multivariate models.
Conclusion
PE conditions affect work performance and employee well-being and may threaten patient care; therefore, it should be further investigated in the care sector. It is noteworthy that calling still seems to be central in care work. The results deepen the understanding of the current shortage crisis in health and social care workplaces but can also provide keys to resolving the crisis.